Analysis of the Cochrane Review: Anticoagulation versus Placebo for Heart Failure in Sinus Rhythm. Cochrane Database Syst Rev. 2014;3:CD003336. - Caldeira, Daniel (2014)
Thrombotic and embolic events contribute to the morbidity and mortality associated to Chronic Heart Failure (HF). Differently from patients with atrial fibrillation (AF) and HF, in which the benefit of anticoagulation is well documented, the use of these drugs in those with HF in sinus rhythm (without AF history) is controversial. In this systematic review from the Cochrane Collaboration, the authors evaluated the benefits and risks associated with oral anticoagulation (versus placebo) in this population. Only 2 randomized controlled trials were published (one with open-label design) enrolling a total of 324 patients. The results of the meta-analysis based on the best available evidence do not support the systematic use of oral anticoagulants in patients with HF and sinus rhythm for preventing death (overall or cardiovascular) or non-fatal cardiovascular events. Furthermore the major bleeding risk was significantly increased.Keywords: Anticoagulation; Heart Failure; Sinus Rhythm; Systematic Review.